Multiple organ dysfunction syndrome associated with Mycoplasma pneumoniae infection - Zhai, Shu-Bo (Sociedade Brasileira de Microbiologia, 2012)
In this study, we report one case of a three-year-old boy infected with Mycoplasma pneumonia (MP) and presenting concomitant multiple organ damage of the heart, kidney, lung and liver, among others, together with a brief review for the diagnosis and treatment of MP infection with multiple organ dysfunction syndrome (MODS).